Analysis of Man 1 Sinjai Students' Participation In Aerobic Physical Activity (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Aerobic physical activity has an important role in improving students' fitness and health. However, the level of participation of MAN 1 Sinjai students in this activity still varies. This study aims to analyse the factors that influence students' participation in aerobic physical activity, including motivation, available facilities, and environmental support, and examine the relationship between students' perceptions of the benefits of aerobic physical activity and the level of students' participation in aerobic activity. This research uses quantitative methods with a descriptive design. The population in this study were MAN 1 Sinjai students, with a sample of 50 students selected using a purposive sampling technique. Data collection techniques were carried out through questionnaires, while data analysis used descriptive statistics. The results showed that the level of student participation in aerobic physical activity varied, with most students showing a fairly good involvement, but there were still those who were neutral towards participation. Motivational factors, sports facilities, and environmental support have a significant effect on student participation, where students who are highly motivated and receive more support tend to be more active. In addition, students' perception of the benefits of aerobic physical activity had a positive relationship with their level of participation. In conclusion, increasing student participation can be achieved with strategies to increase motivation, provide better facilities, and strengthen environmental support. It is hoped that the results of this study can be the basis for designing programs to increase students' physical activity in schools.